New modeling approach of laser communication in constellation and through atmospheric disturbances - Hachemi Chenina; Djamel Benatia; M’ Hamed Boulakroune (Institute of Advanced Engineering and Science, 2021)
Laser communication between satellites in the constellation and from the satellites to ground stations offers a gigantic data rate for the users. This principal advantage drives telecom companies to develop this technology to use it like a carrier signal, the most disadvantage of this technology is the need to very complicated pointing systems between the transmitter and the receiver due to a very small beam divergence, continually moving of satellites in orbits and the distance between the satellites (tens of thousands of kilometers). The laser beam suffers continuously from several factors like atmospheric turbulences, internal and external vibrations. All these factors lead to an increase in the bit errors rate and cause degradation in the communication quality. This paper deals with a new method of modelisation of external effects in transmission of signal light from a ground station to the satellite through atmospheric disturbances. Indeed, an in-depth investigation, of the influences of satellite vibrationsinlaser signal transmission between satellites constellation, has been conducted by studying the effect of the intensity of vibrations on the optical signal amplitude. Some solutions are proposed to improve the efficiency of optical satellites communications.